Impact of concurrent resistance and endurance training upon distance running performance - Nicholson, R. M.; Sleivert, G. G. (Medicine & Science in Sports & Exercise, 1999)
The impact of concurrent resistance and endurance training on 10-km running performance in a simulated competitive situation was investigated. Runners (M = 19; F = 11) were matched and randomly assigned to an experimental (running and resistance) or control (running) group. Ss performed the same training program for 21 weeks, running from 5 to 8 times per week for 30 to 90 minutes at a heart rate intensity ranging from 75 to 95% of maximum. Resistance training involved 3 x 8 repetitions per exercise (intensity level of 8-RM), except for abdominals (15 repetitions). Testing occurred during weeks 3, 9, 15, and 21. The resistance group improved significantly in running time (3.5%), VO2max, lactate threshold velocity, and upper and lower body strength. The running-only group improved in running time (2.2%) and lower body strength. The addition of resistance training did not adversely affect the beneficial effects of running training. It added some extra fitness improvements and might be considered as a beneficial training addition for the basic preparatory phase of a running specialist's annual training plan or by individuals interested in a more generalized fitness program. Implication. Resistance training does not interfere with running training improvements.